Spectral domain optical coherence tomography: a better OCT imaging strategy. (December 2005) - Yaqoob, Zahid; Wu, Jigang; Yang, Changhuei
This paper reviews the current state of research in spectral domain optical coherence tomography (SDOCT). SDOCT is an interferometric technique that provides depth-resolved tissue structure information encoded in the magnitude and delay of the back-scattered light by spectral analysis of the interference fringe pattern. There are two approaches to SDOCT—one that uses a broadband source and a spectrometer to measure the interference pattern as a function of wavelength and the other that utilizes a narrowband tunable laser that is swept linearly in k ∼ 1/λ space during spectral fringe data acquisition. Unlike time domain (TD) OCT, the reference arm is stationary in both SDOCT methods, which allows for ultra high-speed OCT imaging. Owing to its high speed and superior sensitivity, SDOCT has become indispensable in biomedical imaging applications. After a brief introduction and a discussion on sensitivity advantage, methods of implementation of the two SDOCT schemes will be presented. The two peer approaches are compared in speed, scan depth range, complexity, spectral regions of operation, and methods of detection. The review also discusses OCT enhancements and functional methods based on SDOCT format and concludes with possible directions that this research may take in the near future.